Blood clotting profiles of haruan fish (channa striatus sp.) aqueous extract - Soo, Kuan Meng (2012)
Dietary therapy is the practical application of nutrition to prevent or treat disease. It has been introduced to maintain a normal haemostatic function, as a complement to drug therapy. Among all, Channa striatus sp. fish is traditionally used as dietary treatment in ameliorating wound lesions in post partum involution. Although studies have been done to prove that Channa striatus sp. fish is able to enhance remodeling and proliferation of tissue (second and third stage of wound healing), its effects towards haemostasis are not fully understood (first stage of wound healing). Thus, this study aims to identify the effects of aqueous extraction of Channa striatus sp. fish towards haemostasis. Experimental design: This study has been approved by ethical committee of Universiti Putra Malaysia. 10 ml blood sample is collected from 9 (platelet aggregation assay), 16 (coagulation assay) and 21 (coagulation factor assay) healthy male or female respondents aged between 16-36 years and weighed between 40 to 70 kg. Written consent is obtained. (A) Aggregation test, whole blood is withdrawn from 9 respondents and each is divided into 4 groups. Group 1, 2, 3 and 4 consist of negative control, 0.25mg/ ml, 1.25mg/ ml and 2.50mg/ ml concentration of aqueous extraction of Channa striatus sp. fish is used in group 1, 2, 3 and 4, respectively. Responses of each group towards platelet agonists (ADP, collagen, arachidonic acid and ristocetin) are tested. (B) Coagulation assay, the platelet poor plasma is used. The plasma is withdrawn out from 16 respondents and is divided into 5 groups. 0%, 10%, 20%, 30% and 40% of aqueous extraction of Channa striatus sp. fish is used in group 1, 2, 3, 4 and 5 respectively; activated partial thromboplastin time (APTT) and prothrombin time (PT) are carried out. (C) Coagulation factor assay, platelet poor plasma is withdrawn from 21 respondents and is divided into 4 groups. 0 mg/ ml, O.25mg/ ml, 0.50mg/ ml, O.75mg/ ml concentration of aqueous extraction of Channa striatus sp. fish is used in group 1, 2, 3 and 4 respectively. Percentage activities of coagulation factor II, fibrinogen, V, VII, VIII, X, XI, XII, after each group of treatment are analyzed. Data interpretations: Results were expressed in means (:t s.e.m.) and analyzed statistically by using paired-t test for all the experiments. Correlations between concentration of HTE and its effects towards haemostasis marker are done. Results: The extract showed significant effects in inhibiting the platelet aggregation induced by platelet agonist adenosine diphosphate (ADP), collagen, arachidonic acid and ristocetin, but did not show significant effects in activating the coagulation pathway and coagulation factor activity.